Grip strength is a strong predictor of survival in nonagenarians and centenarians - Marlon Cassio Pereira Grigol; Patricia Morsch; Ângelo José Gonçalves Bós (Brazilian Society of Geriatrics and Gerontology, 2022)
Objectives: To understand the importance of hand grip strength (HGS) as a survival predictor in nonagenarians and centenarians. Methods: Longitudinal, observational and analytical study, using HGS measurements obtained during a first evaluation performed in 2016. Participants were nonagenarians and centenarians, randomly selected in various neighborhoods of Porto Alegre (RS) and evaluated in their homes. The time elapsed between the first evaluation and the date of death or last contact (for survivors) was used to calculate the hazard ratio (HR) using survival analysis on simple and adjusted Cox regression models. Results: The sample comprised 212 participants (155 women), of whom 83 (39%) died during follow-up (until August 30, 2019). Using the lowest quartile (25%) for HGS, participants with < 10 kgf for women and 17 kgf for men were considered to have poor HGS performance. In the simple regression model, participants with lower HGS presented a HR of 2.75 (1.76-4.30, p < 0.001) for death. Also in the simple model, participants aged between 90 and 94 years old presented an HR of 0.37 (0.16-0.85, p = 0.019) compared to those aged 100 or older. In the adjusted model, age lost its significance in the presence of HGS. The following were significant predictors in both simple and adjusted models: cognitive performance, calf circumference, ability to participate in social activities, shop, and prepare meals alone, performance in the Timed Up and Go test, and ease to perform activities requiring upper limb strength. Conclusions: HGS was an important independent and modifiable predictor of survival among nonagenarians and centenarians.